2023
DOI: 10.1371/journal.pone.0287580
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus seroprevalence, testing, and treatment capacity in public health facilities in Ghana, 2016–2021; A multi-centre cross-sectional study

Yvonne Ayerki Nartey,
Rafiq Okine,
Atsu Seake-Kwawu
et al.

Abstract: The current burden of Hepatitis C virus infection and the availability of HCV-related services in Ghana are not well described. Previous estimates on HCV seroprevalence in the country are outdated. This study investigated the HCV seroprevalence and testing and treatment capacity in Ghana. A multi-centre cross-sectional study was conducted in which laboratory and blood bank registers from 17 public healthcare institutions in Ghana were reviewed. A survey on cost and availability of HCV-related testing and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…According to the Polaris Observatory Network, there are currently an estimated 440,000 people living with chronic HCV infection in Ghana, 9% of whom have been diagnosed with less than 1% treated annually. Previous systematic review reported HCV prevalence of 3% in Ghana with a recent nationwide auditing of hospital records estimating the prevalence at 4.6% (Agyeman et al, 2016; Nartey et al, 2023). The proportion from our study with HCV seropositive of 1.85% was less than these estimates but closer to the prevalence of 2.7% reported by a study undertaken previously in Cape Coast, the locale for our study (Tetteh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the Polaris Observatory Network, there are currently an estimated 440,000 people living with chronic HCV infection in Ghana, 9% of whom have been diagnosed with less than 1% treated annually. Previous systematic review reported HCV prevalence of 3% in Ghana with a recent nationwide auditing of hospital records estimating the prevalence at 4.6% (Agyeman et al, 2016; Nartey et al, 2023). The proportion from our study with HCV seropositive of 1.85% was less than these estimates but closer to the prevalence of 2.7% reported by a study undertaken previously in Cape Coast, the locale for our study (Tetteh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Because the HCV RNA determination was not undertaken in this study, we were unable to determine the proportion of the HCV positive individuals who would have needed treatment. The cost of viral load estimation in Ghana is high, with ancillary tests including HCV genotyping and liver fibrosis status (using FIB-4, APRI, liver elastography and liver biopsy) adding up additional cost to the patients (Nartey et al, 2023). The introduction of the curative DAAs for HCV treatment makes it imperative that population screening ought to be scaled up especially among high-risk groups, including incarcerated individuals, people who inject drugs and children born to mothers with HCV.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1,769 individuals were included in the study. Using Cochran’s formula [ 16 ] with a 95% confidence level and an estimated proportion of 14.4% based on previously reported seroprevalence [ 10 ], the minimum sample size required was 190. Participants were consented based on convenience sampling, with screening offered to inhabitants of the nine communities visited as part of World Hepatitis Day 2022—related activities in the district.…”
Section: Methodsmentioning
confidence: 99%
“…In Ghana, the prevalence of HCV antibody was reported at 3.0% in a systematic review comprising hospital-based and limited community-based studies in 2016 [ 9 ]. Furthermore, hospital-based data from Ghana demonstrated a crude anti-HCV prevalence of 2.6% [ 10 ], and HCV is associated with 6.4% of Hepatocellular Carcinoma (HCC) [ 11 ] cases and 7% of liver-related deaths [ 12 ]. Previous studies on HCV in Ghana have primarily relied on hospital-based data, which may limit our ability to determine prevalence in the general population, therefore there is a need for community-based studies to better characterize the burden of infection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation